2019
DOI: 10.1002/biof.1539
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DGCR5 regulates the non‐small cell lung cancer cell growth, migration, and invasion through regulating miR‐211‐5p/EPHB6 axis

Abstract: Non‐small cell lung cancer (NSCLC) accounts for about 80% of lung cancers worldwide. In recent years, importance of noncoding RNAs including long noncoding RNA and microRNA in regulating tumor progression has been appreciated. Abnormally expression of DiGeorge syndrome critical region gene 5 (DGCR5) was found in multiple human cancers but its function in NSCLC is largely unknown. Reverse transcription quantitative polymerase chain reaction (RT‐qPCR) was conducted to explore DGCR5 expression level in NSCLC. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…We used the GEO database to select mRNAs that were downregulated in SOC, identified potential lncRNA-miRNA-mRNA interaction networks based on the presence of specific binding sites, and reconstructed a comprehensive ceRNA network. Several recent studies demonstrated that ceRNA-based mechanisms may operate in all types of carcinoma [5,6,[17][18][19][20][21][22][23]. In the present study, among the miRNAs found to be downregulated in SOC, hsa-miR-195-5p and hsa-miR-497-5p were predicted to bind to LINC00284.…”
Section: Discussionsupporting
confidence: 54%
“…We used the GEO database to select mRNAs that were downregulated in SOC, identified potential lncRNA-miRNA-mRNA interaction networks based on the presence of specific binding sites, and reconstructed a comprehensive ceRNA network. Several recent studies demonstrated that ceRNA-based mechanisms may operate in all types of carcinoma [5,6,[17][18][19][20][21][22][23]. In the present study, among the miRNAs found to be downregulated in SOC, hsa-miR-195-5p and hsa-miR-497-5p were predicted to bind to LINC00284.…”
Section: Discussionsupporting
confidence: 54%
“…Considering that lncRNAs are reported to take part in the regulation of gene expression via many kinds of mechanisms, such as suppression of gene translation, degradation of microRNAs, the elevation of chromatin modification, modulation of protein activity, and so on (Jarroux, Morillon, & Pinskaya, 2017). DGCR5 has been discovered to attend to the regulation of microRNA-22-3p (Dong, Wang, Jin, Zeng, & Pan, 2018), microRNA-346/kruppel-like factor (KLF14; Wang, Liu et al, 2019), microRNA-873-5p/tumor suppressor candidate 3 (TUSC3; Luo et al, 2018), microRNA-221-5p/EPH receptor 6 (EPHB6; Kang et al, 2019) and miR-195 (Tang, Shan, & Zeng, 2019). We can propose that some miRNAs are involved in the regulatory mechanisms of DGCR5 on Raf1/ERK1/2 and Wnt/βcatenin pathways in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, miR‐124‐3p acted as an inhibitory factor in tumors. Additionally, a great number of studies have manifested that lncRNA could exert ceRNA function to regulate miRNA . Accordingly, we discovered that LINC01410 modulated miR‐124‐3p as a ceRNA to promote CCA development.…”
Section: Discussionmentioning
confidence: 97%